Characterization of 23 polymorphic SSR markers in Salix humboldtiana (Salicaceae) using next‐generation sequencing and cross‐amplification from related species - Bozzi, Jorge Alfredo; Liepelt, Sascha; Ohneiser, Sebastian; Gallo, Leonardo Ariel; Marchelli, Paula; Leyer, Ilona; Ziegenhagen, Birgit; Mengel, Christina (Botanical Society of America, 2019)
Premise of the study: We present a set of 23 polymorphic nuclear microsatellite loci, 18 of which are identified for the first time within the riparian species Salix humboldtiana (Salicaceae) using next‐generation sequencing. Methods and Results: To characterize the 23 loci, up to 60 individuals were sampled and genotyped at each locus. The number of alleles ranged from two to eight, with an average of 4.43 alleles per locus. The effective number of alleles ranged from 1.15 to 3.09 per locus, and allelic richness ranged from 2.00 to 7.73 alleles per locus. Conclusions: The new marker set will be used for future studies of genetic diversity and differentiation as well as for unraveling spatial genetic structures in S. humboldtiana populations in northern Patagonia, Argentina.